PENGARUH PERSEPSI SISWA TENTANG KOMPETENSI PROFESIONAL GURU SEJARAH TERHADAP HASIL BELAJAR SISWA KELAS X DI SMAN 1 RANGSANG TAHUN AJARAN 2019/2020 - Alfiah, Alfiah; Isjoni, Isjoni; Tugiman, Tugiman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: SMAN 1 Rangsang is one of the state schools founded in 2002 with Bengkalis Regent Decree Number: III dated January 1, 2002. This study aims to (1) students' perception of the professional competence of class X history teachers at SMAN 1 Rangsang grade academic year to be determined 2019/2020, (2) Learning outcomes of students in class X history subjects at SMAN 1 Rangsang out the school year 2019/2020, (3) Determine the effect of students' perception of the professional competence of the history teacher on learning outcomes of students in class X at SMAN 1 Rangsang the school year 2019/2020. In this study, the independent variable is students' perception of the professional competence of the teacher (X) and the dependent variable is the student's learning outcomes (Y). The research approach used in this research is quantitative research using research methods, using simple linear regression analysis. The subjects of this study were students at SMAN 1 Rangsang, namely class X, with a total of 83 students. The results obtained showed that the percentage is classical which is equal to 87.77%. Learning outcomes in the history subjects of class X in SMAN 1 Rangsang the school year 2019/2020, based on the general learning outcomes of the student, completeness has been achieved. The criterion of the degree of relationship coefficient is 0.497, which means that the teacher's professional ability has a moderate relationship due to the value of the Pearson correlation from 0.41 to 0.70. The higher the professional competence of history teachers, the higher the learning outcomes of Grade X students at SMAN 1 Rangsang. Based on simple linear regression analysis, the regression coefficient is known to be positive with the regression equation Y = 50,807 + 0.297X, meaning students' perception of professional competence of teachers (X) has a positive effect on learning outcomes (Y). Significant value of 0.000  0.05, so it can be concluded that H0 is rejected, meaning that "There is an effect of students' perception of teacher competence (X) on student learning outcomes (Y)". R Square value of 0.247, which means that the contribution of the variable perceptions of the professional competence of teachers (X) to the variable learning outcomes of students (Y) was 24.7%.Key Words: Influencing Students 'Perceptions of Teachers' Professional Competence VersusStudent Learning Outcomes At SMAN 1 Rangsang